PENGARUH JENIS BAHAN PEREKAT DAN METODE PENGERINGAN TERHADAP KUALITAS BRIKET LIMBAH BAGLOG JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Siti Mushlihah; Sulfahri; Renia Setyo Utami; Eko Sunarto; I.D.A.A. Warmadewanthi (The East Java Biological Society, 2011)
White mushroom is one of popular food commodity in East Java. Every year total production of white mushroom is more than 4800 ton. The cultivation of this mushroom needed the medium known as